2018
DOI: 10.15640/jsbed.v6n2a2
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Human Capacity Building on Small and Medium Enterprises in Lagos, Nigeria

Abstract: The major aim of this article is to examine the impact of the Human Capacity Building on Small and medium enterprises in Lagos, Nigeria. The study design was quantitative. Data was gathered from 139 respondents selected from entrepreneurs small and medium enterprises in Lagos. SPSS was used to analyze the data gathered. Findings from the study reveal that regulatory constraints, accessibility to credit and low marketing skills are the top three barriers to the SMEs owners business. Financial management, market… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…On the other hand, laissez-faire leadership, characterized by minimal guidance and allowing employees to make decisions independently, may not be suitable for all situations (Oladipo, Isah, & Adamolekun, 2018). In the food and beverages sector, where operational efficiency and quality control are critical, an excessive laissezfaire leadership style may result in inconsistency, lack of direction, and reduced entrepreneurial success.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, laissez-faire leadership, characterized by minimal guidance and allowing employees to make decisions independently, may not be suitable for all situations (Oladipo, Isah, & Adamolekun, 2018). In the food and beverages sector, where operational efficiency and quality control are critical, an excessive laissezfaire leadership style may result in inconsistency, lack of direction, and reduced entrepreneurial success.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies have examined the relationship between leadership style and entrepreneurial success indicators in SMEs. Oladipo, Isah, and Adamolekun (2018) conducted a study on the impact of leadership style on the performance of small and medium-sized enterprises in Nigeria. Their findings revealed that transformational leadership had a positive influence on SME performance, including profitability and growth.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Human capital is indispensable in the development of a nation, they are the engines that move the nation forward either in private or public capacity, and they are significant in the following aspects as indicated in (Aladejebi, 2018).…”
Section: Importance Of Human Capacity Buildingmentioning
confidence: 99%
“…It is believed that managers and business owners with longer years of experience can more quickly identify and process opportunities and risks in the market. Building and developing industry knowledge through practical on the job management is seen to be more effective than formal and theoretical trainings(Aladejebi, 2018). There are other research works, for example, who disagree that human capital and quality of the management adds positive value to the growth of a firm.…”
mentioning
confidence: 99%